Three-year clinical outcomes of relapsing multiple sclerosis patients treated with dimethyl fumarate in a United States community health center. (June 2018) - Smoot, Kyle; Spinelli, Kateri J; Stuchiner, Tamela; Lucas, Lindsay; Chen, Chiayi; Grote, Lois; Baraban, Elizabeth; Kresa-Reahl, Kiren; Cohan, Stanley
Background: Following approval of dimethyl fumarate (DMF), we established a registry of relapsing multiple sclerosis (RMS) patients taking DMF at our community MS center. Objective: To track DMF patients' tolerability, disease progression, and lymphopenia. Methods: Patients prescribed DMF for RMS from March 2013 to March 2016 were prospectively enrolled ( N = 412). Baseline data, clinical relapses, magnetic resonance imaging (MRI) activity, discontinuation, and lymphocyte counts were captured through chart review. Results: The mean age of patients starting DMF was 49.4 ± 12.0 years and 70% transitioned from a previous disease-modifying therapy (DMT). Of the patients, 38% discontinued DMF, 76% of whom discontinued due to side effects. Clinical relapse and MRI activity were low. Comparing patients who transitioned from interferon-β (IFN), glatiramer acetate (GA), or natalizumab (NTZ), patients previously on NTZ had higher rates of relapse than those previously on GA (annualized relapse rate p = 0.039, percent relapse p = 0.021). Grade III lymphopenia developed in 11% of patients. Lymphopenia was associated with older age ( p < 0.001) and longer disease duration ( p < 0.001). Conclusion: Given the high rates of lymphopenia and discontinuation, it has become our clinical practice to more closely scrutinize older patients and those with a longer disease duration who are potential candidates for initiating DMF therapy.